Soil nitrogen absorption by corn as affected by crop residues addition - Demétrio, Ronaldo; G. Marinho Guerra, José; de Araújo Santos, Gabriel; Lopes de Almeida, Dejair; de-Polli, Helvécio; A. de Oliveira Camargo, Flávio (Pesquisa Agropecuaria Brasileira, 1998)
Various levels of Canavalia brasiliensis and Panicum maximum (20, 40 and 60 t.ha-1) were incorporated into a red-yellow podzolic soil, which was planted with corn. After 102 days in the greenhouse, the C, N, and organic matter fractions content of the soil and the N level dry matter of the plants were measured. One ton of Canavalia brasiliensis or Panicum maximum produced a linear increase of 0.088 or 0.068 mg C.g-1 soil, respectively. The C content of the alkali-soluble soil fraction of the humic fraction was unaltered, but was increased in the humin and free organic material fractions, especially by Canavalia brasiliensis. Nitrogen content increased linearly with the application of one ton of Canavalia brasiliensis or Panicum maximum to 0.0103 or 0.004 mg N.g-1 soil, respectively. There was a rise in the free fulvic acid fraction in soil treated with 40 and 60 t.ha-1 of Canavalia brasiliensis, compared with the control. Canavalia brasiliensis increased the N content of the soil and enhanced the N content of the corn to a level equivalent to that obtained with the application of 560 kg.ha-1 of N.